Why study the future of criminal justice? - Stephens, Gene (American journal of criminal justice, 1980)
To a large, extent criminal justice agencies are reactive in nature and thus are at the mercy of evants beyond their control. The author suggest that use of futures research and forecasting methods, followed by development of policy alternatives through futures planning techniques, will aid agencies in becoming proactive —being able to anticipate future trends and develop and choose among alternative policies demed most beneficial to achievement of the goals and objectives of the agency. Some techniques of futures research are discussed as is the efficacy of presentation of findings in the form of scenarios.